Photocatalytic degradation of triclocarban in artificial bathroom greywater by modified tio₂ nanotubes coated with zeolite (TNTs/ZEO) - Arifin, Siti Nor Hidayah (2021)
Xenobiotic organic compounds (XOCs) originated from anti-microbial personal care products (PPCPs) including triclocarban (TCC) are emerging contaminants can cause hazardous effect on water environment. The study aims to measure the degradation of the XOCs which is TCC to promote water quality protection measures. Hence, objective of this research is to study the photocatalytic degradation of TCC in greywater. Photocatalytic degradation was enhanced by modification of photocatalyst which is TiO₂ nanotubes with the coating of zeolite (TNTs/Zeo). TNTs/Zeo catalyst were formed by application of electrochemical anodization (ECA) for TiO₂ nanotubes formation and electrophoresis deposition (EPD) in coating zeolite. The characteristics of catalyst were verified using FESEM/EDS, and XRD. In order to control the presence of TCC, the optimization of photocatalytic degradation of TCC was designed via factorize central composite design (FCCD) design matrix of RSM by depending on pH value (3 - 10), TNTs/Zeo catalyst loading size (0.5 cm² - 1.0 cm²) and irradiation time (10 - 60 minutes) as variables. The photocatalytic degradation experiments have been conducted under natural sunlight radiation. The overall finding has directed to the pH value 11, TNTs/Zeo catalyst loading 0.75 cm², and irradiation time 50 minutes were the optimum conditions of photocatalytic degradation on TCC that has provided the maximum efficiency of photocatalytic degradation up to 81.2 % removal of TCC concentration. Based on kinetic study by following Langmuir-Hinshelwood (L-H) model and pseudo first order, the significant constant rate obtained at pH 11 which was 0.048 ppm/min, 0.75 cm² of TNTs/Zeo catalyst loading size achieved 0.047 ppm/min and 5 ppm of TCC initial concentration reached 0.037 ppm/min. Furthermore, there eleven intermediate products were detected after the whole process of photocatalysis. In addition, the photocatalytic degradation rate of TCC from first and fifth cycles were 94.2 % and 77.4 % where it still can be considered as significant TCC degradation rate.